Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Vinay
Lv 4
Vinay asked in Science & MathematicsMathematics · 9 years ago

Plzzz prove this... divisibility !!!!!!!!?

prove that 13^(2n + 1) + 9^(2n + 1) is divisible by 22 by the process of divisibility ?

3 Answers

Relevance
  • Fred
    Lv 7
    9 years ago
    Favorite Answer

    Probably the easiest way to get that result is modular arithmetic.

    Modulo 22, 9 and 13 are opposites:

    13 == -9 mod 22

    because 13 + 9 = 22

    So raising both to any odd power,

    13^(2n+1) == (-9)^(2n+1) == (-1)^(2n+1) • 9^(2n+1) == -[9^(2n+1)]

    thus,

    13^(2n+1) + 9^(2n+1) == 0 mod 22

    QED

    EDIT:

    This same method will prove Madhukar's generalization of this proposition.

    @ oregfiu: Nice proof! But the starting condition is even easier with n=0 !

    oregfiu's method will also prove Madhukar's generalized proposition.

  • 9 years ago

    Let 2n + 1 = m

    Obviously, m is an odd number

    => 13^m + 9^m

    = (13 + 9) * [(13)^(m-1) - (13)^(m-2) * (9) + (13)^(m-3) * (9)^2 - ... + (9)^(m-1)]

    As this has a factor 22, the number is divisible by 22.

    Edit:

    In general, one can say that

    a^m + b^m is divisible by (a + b) if m is odd.

  • 9 years ago

    Proof by mathematical induction:

    1st step:

    For n=1

    13^(2*1 + 1) + 9^(2*1 + 1) = 2926 = 22 * 133

    2nd step:

    Suppose that

    13^(2k + 1) + 9^(2k + 1) = 22 N

    where N is natural number.

    Then

    13^(2(k+1) + 1) + 9^(2(k+1) + 1) =

    = 13^2 * 13^(2k + 1) + 9^2 * 9^(2k + 1) =

    = 169 * 13^(2k + 1) + 81 * 9^(2k + 1) =

    = (81 + 88) * 13^(2k + 1) + 81 * 9^(2k + 1) =

    = 81 * 13^(2k + 1) + 81 * 9^(2k + 1) + 88 * 13^(2k + 1) =

    = 81 (13^(2k + 1) + 9^(2k + 1)) + 88 * 13^(2k + 1) =

    = 81 * 22 N + 88 * 13^(2k + 1) =

    = 22 (81 N + 4 * 13^(2k + 1))

    Q.E.D.

    -

Still have questions? Get your answers by asking now.